Zimbabwe : Technical Assistance Report-Undertaking Supervisory Examinations Remotely Due to COVID-19 Operational Restrictions. (IMF Staff Country Reports; Country Report ;, 2022)
The RBZ is in the process of recommencing on-site examinations, but due to COVID-19 operational restrictions, these will need to be undertaken remotely. The RBZ has developed a draft remote examination framework document to guide this work and requested AFS assistance to review the framework, and also provide information on how other supervisors are undertaking examinations remotely. The mission provided training on international practice of remote examinations, which was presented by supervisors from the Bank of Ghana (BOG), Bank of Thailand (BOT) and the De Nederlandsche Bank (DNB) and reviewed the draft remote examination framework document. The training covered adjustments to examination framework and operational issues and key points of consideration when undertaking examinations remotely. The mission also reviewed the RBZ consolidated examination manual, to provide feedback to the RBZ on the feasibility of undertaking supervisory examinations remotely, as described in the manual and provide points for consideration for undertaking such examination remotely.